PEGARUH PENDEKATAN REALISTIKC MATHEMATIC EDUCATION TERHDAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMSP N28 MERANGIN - hasmawati hasmawati (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
This research is motivated by the low learning outcomes of class VII students. From the indicators of mathematics learning outcomes, there are several indicators of students' mathematics learning outcomes that still cannot be achieved. This is because students think mathematics is a difficult subject, and teachers teach too monotonously so that students become less active and teachers still use conventional learning. Therefore, the researcher offers a Realistic Mathematical Education learning model to overcome the above problems. The purpose of this study was to determine and describe the learning outcomes of mathematics applied by Realistic Mathematical Education which was better than that applied to conventional learning. Grade VII students of SMP N28 Merangin. This research uses a quantitative approach with experimental methods and uses a Posttest-Only-Control Design research design. The population in this study were students of class VII SMP N 28 Merangin and sampling using saturated sampling technique, the sample selected as the experimental class was class VII A, control class was class VII B. The research instrument was in the form of descriptions and data analysis techniques using t-test . From the final test, the results of data analysis were obtained with the average value of the sample class students using the Realistic Mathematical Education learning model was 71.89, while the control class obtained an average of 53. The data analysis technique used to test the hypothesis was t-test, because the data is normally distributed and the variance is homogeneous. The results of the hypothesis obtained t_count = 6.87 and t_table = 2,920. Because t_count>t_table, Ho is rejected and Ha is accepted. The conclusion of this study is that the learning outcomes of mathematics taught using the Realistic Mathematical Education learning model are better than the results of learning mathematics taught using conventional learning for class VIII students of SMP N 28 Merangin.